A227 UNDERSTANDING ACCESS TO IBD SPECIALTY CARE IN NOVA SCOTIA THROUGH THE PATIENT LENSE. (1st March 2018) - Heisler, C; Mathias, H; Morrison, J B; Kits, O; Veldhuyzen van Zanten, S; Jones, J
Abstract: Background: Inflammatory Bowel Disease (IBD) is a chronic immune-mediated disease with significant societal burden. The highest age and sex-adjusted standardized incidence and prevalence estimates of IBD have been observed in Canada, with Nova Scotia exhibiting the highest rates in the country. Despite this burden, Canadians living with IBD often face access barriers when seeking gastroenterology specialty care. Aims: To examine IBD care access through the patient perspective in order to identify barriers and facilitators for equitable and efficient access to gastroenterology specialty care in Nova Scotia. Methods: A peer-reviewed and patient-piloted questionnaire was developed through extensive consultation with clinicians, epidemiologists, nurse practitioners (NP), and patients. Questionnaires were developed using evidence-based principles and included demographic, disease, referral structure, and referral process-related questions. The survey was administered using a stratified, random sampling approach to ensure geographic representation. Questionnaires were completed by patients presenting to the Nova Scotia Collaborative IBD Program following their appointment with a luminal GI clinician or IBD NP. Results: As of October 2017, 33 respondents completed questionnaires (sample target: 372). Twenty patients were female (20/33, 61%), mean age of 44 years (SD=16.7, range 19–76 years). Crohn's disease was the most common diagnosis (20/33, 61%), with patients experiencing symptoms between 1 month and 8 years before being seen by a specialist. The majority of patients (25/33, 76%) reported using healthcare services to manage their IBD while waiting to see a specialist, including emergency room services and walk-in clinics. Approximately 20% (7/33) of patients reported that most or all of their appointments were located outside of their community, with a mean wait time of 3–6 months for a specialist appointment. Patients identified long wait times (17/33, 52%), limited resources (e.g. lack of a GI specialist in their community) (10/33, 30%), and poor communication (e.g. lack of communication between patient, referring physician, and specialist) (7/33, 21%) as major access barriers. The top three recommendations by patients for improved access to care were being able to contact the specialists' office to notify them of worsening symptoms (15/33, 46%), receiving direct communication about wait times and appointments (14/33, 42%), and ability to self-refer (9/33, 27%). Conclusions: This is one of the first studies conducted which examines access to gastroenterology IBD specialty care from the patient perspective. Our findings show clear patient-perceived barriers to accessing IBD specialist care in Nova Scotia with long wait times despite a high medical need. Survey administration is ongoing. Funding Agencies: CIHRNova Scotia Health Authority Research Fund